Reductions in neuronal peroxisomes in multiple sclerosis grey matter. (May 2014) - Gray, Elizabeth; Rice, Claire; Hares, Kelly; Redondo, Juliana; Kemp, Kevin; Williams, Marcus; Brown, Ann; Scolding, Neil; Wilkins, Alastair
Background: Peroxisomes are organelles in eukaryotic cells with multiple functions including the detoxification of reactive oxygen species, plasmalogen synthesis and β-oxidation of fatty acids. Recent evidence has implicated peroxisomal dysfunction in models of multiple sclerosis (MS) disease progression. Objectives: Our aims were to determine whether there are changes in peroxisomes in MS grey matter (GM) compared to control GM. Methods: We analysed cases of MS and control GM immunocytochemically to assess peroxisomal membrane protein (PMP70) and neuronal proteins. We examined the expression of ABCD3 (the gene that encodes PMP70) in MS and control GM. Analyses of very long chain fatty acid (VLCFA) levels in GM were performed. Results: PMP70 immunolabelling of neuronal somata was significantly lower in MS GM compared to control. Calibration of ABCD3 gene expression with reference to glyceraldehyde 3-phsophate dehydrogenase (GAPDH) revealed overall decreases in expression in MS compared to controls. Mean PMP70 counts in involved MS GM negatively correlated to disease duration. Elevations in C26:0 (hexacosanoic acid) were found in MS GM. Conclusions: Collectively, these observations provide evidence that there is an overall reduction in peroxisomal gene expression and peroxisomal proteins in GM neurons in MS. Changes in peroxisomal function may contribute to neuronal dysfunction and degeneration in MS.